Implications of Extension of the Term of Office of the Village Head Based on Law No. 3 of 2024 Concerning the Second Amendment to Law No. 6 of 2014 Concerning Villages Towards the Principles of Democracy in Kerato Village - Rizka Febriana; Syarif Dahlan; Noviana Noviana (International Journal of Law, Crime and Justice, 2025)
Regulatory changes through Law No. 3 of 2024 concerning the Second Amendment to Law No. 6 of 2014 stipulate an extension of the village head's term of office from six to eight years. This policy is intended to strengthen leadership stability and the sustainability of village development, but also raises concerns regarding reduced leadership circulation, weakened community political participation, and increased potential for abuse of power. This research uses empirical legal methods with sociological, conceptual, and case-based approaches, conducted through field observations and in-depth interviews with village officials, community leaders, MSMEs, and residents of Kerato Village. The results show a diverse response from the community. Some support this policy because it is seen as providing the village head with the opportunity to complete development programs sustainably. However, others reject it, arguing that term extension has the potential to reduce the quality of local democracy, limit leadership regeneration, and reduce the frequency of community political participation. The discussion emphasizes the dilemma between village government stability and the principles of participatory democracy. In conclusion, this policy is ambivalent: positive in maintaining development continuity, but risky for accountability and community participation. Therefore, strengthening the function of the Village Consultative Body (BPD), transparency, and effective oversight mechanisms are very necessary to maintain the balance between government stability and village democracy.